DESIGN OF DIGITAL IMPACTING FILTER IN CP-EBPSK WITH RANDOM-POLAR COMMUNICATION SYSTEM - Jin, Yi; Wu, Lenan; Chen, Yifang; Yu, Jing (Journal of electronics (China), 2012)
To solve the difficulty of designing digital impacting filter in the receiver of random-polar modulated Extended Binary Phase Shift Keying with Continuous Phase （CP-EBPSK）, a design method based on Quantum-behaved Particle Swarm Optimization （QPSO） algorithm is proposed. Firstly, QPSO is introduced elaborately, and the basic flow of QPSO is Mso given. Then, the de- modulation principle of digital impacting filter in the communication system of CP-EBPSK with random-polar is demonstrated, and QPSO is utilized to design the digital impacting filter, which also takes the effect of finite word length into consideration when implemented by hardware. Finally, the proposed method is simulated. Simulation results show that the digital impacting filter designed by new method can derive satisfied demodulation performance.